Le voyage dans l’Andalousie hispano-musulmane : miroirs romantiques et orientalistes à l’épreuve (1880-1914) - Daniel Lançon (Viatica)
Corpus study focuses on the evolution of travel in the high places of a province considered by French-speaking scholars as an Eastern Elsewhere on the edge of Europe. Experience of the sublime, fascination with ornamentation, praise for orientalist restorations lead to a nostalgic celebration of monumental Andalusia until the turn of the century, based on the belief in the continuity of the ancient inhabitants of al-Andalus to contemporary Andalusians and largely over determined by the desire to escape the social constraints of a modernizing Europe. The rise of identity anxiety in Europe and the emergence of voices of oriental travellers, pilgrims of faith and no longer of art or young activists of the revival of oriental nations, inaugurate a new period.